Head, Neck and Oral Cancer Examination - Michael A. Siegel; Dominic M. Aloise; Valerie Murrah (Association of American Medical Colleges, 2009)
Abstract This 40-minute video is intended for practitioners of dentistry, medicine, nursing, and public health who are responsible for diagnosing and referring patients with head and neck and oral cancer. Approximately 31,000 cases of oral and head and neck cancer are diagnosed in the United States yearly, and about 25% of these patients die from their disease. Most of these tumors represent squamous cell carcinoma of the oral mucous membranes. The combined 5-year survival rate in the United States is approximately 57%. A squamous cell carcinoma found in stage 1 has a 5-year prognosis of 95%, while the same tumor diagnosed in stage 4 has a 5-year prognosis of approximately 20%. The purpose of this video is to provide the practitioner with the baseline skills to diagnose and refer patients with head and neck and oral cancer at the earliest possible time. Dentists and physicians (students and licensed practitioners) will thereby have a means of providing patients with a complete head and neck and oral examination. This will allow these cancers to be diagnosed at the earliest possible time, thus increasing the prognosis and decreasing morbidity and mortality.